Etos Kerja Guru PAK sebagai Fondasi Pembentukan Karakter Siswa di SMPN 4 Tuhemberua, Nias Utara - Swan Kariawati Laoli (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
This study aims to analyze the role of Christian Religious Education (PAK) teachers' work ethic in character building of students at SMP Negeri 4 Tuhemberua, North Nias Regency. The work ethic possessed by a teacher not only affects the quality of learning, but also has a significant impact on the formation of students' character, in terms of discipline, responsibility, and integrity. PAK teachers have a strategic role in instilling moral and spiritual values ​​through role models and teachings applied in everyday life. This study uses a qualitative approach with a literature study method to describe the work ethic of PAK teachers that contributes to the formation of students' character. The results of the study indicate that the work ethic of PAK teachers, which includes exemplary behavior, discipline, and commitment to the profession, has an impact on the formation of students' character at SMP Negeri 4 Tuhemberua. Students who are equipped with the basic work ethic of teachers show an increase in attitudes of discipline, responsibility, and honesty. The conclusion in this study is that strengthening the capacity of PAK teachers in integrating work ethic in all aspects of learning is useful for supporting the formation of students' character.